KPC Carbapenemase-producing Enterobacteriaceae isolated in a Maracaibo’s Hospital, Venezuela - Liliana Gómez Gamboa; Armindo Perozo Mena; Judith Lugo; José Bermúdez González; Irene Zabala; Ever Morales (Kasmera, 2014)
Carbapenems have generally been considered the pharmacotherapy of last resort for managing infections associated with health services caused by multidrug-resistant gram-negative bacteria. However, it is worrisome that this situation is being threatened worldwide with the appearance of bacterial strains that resist these antibiotics due to the production of novel B-lactamases with direct carbapenem-hydrolyzing activity (carbapenemases). This study was performed to characterize KPC carbapenemase-producing Enterobacteriaceae isolated from a hospital in the Zulia region during 2009-2013 in terms of their geno- and phenotypes. KPC carbapenemase production was detected in 423 strains of carbapenem-resistant Enterobacteriaceae (36.29%). The most affected patients were male adults from the intensive care unit. The most common site of colonization was the respiratory tract, while rectal carrier status was rare. These KPC carbapenemases were detected mainly in K. pneumoniae, K. oxytoca, E.coli and E. cloacae. Most isolates showed multidrug-resistance and an extensively drug-resistant phenotype. The majority of the phenotypic methods were effective for the detection of KPC producers  in Enterobacteriaceae isolates and the presence of blaKPC gene confirmed that the Carbapenemase circulating in Enterobacteriaceae strains in this region are the KPC type.